Developing Land in Florida with Fire in Mind: Recommendations for Designers, Developers, and Decision Makers - Martha C. Monroe; Susan Marynowski (EDIS, 2012)
In 1998, fire destroyed or damaged 330 homes and businesses in Florida. Losses totaled more than $800 million. In some places, homes were saved by fire-fighting crews, or where the right decisions were made by builders or designers. With advance planning, architects and developers can do a great deal to reduce wildfire risk for those living and working in Florida. This revised 5-page fact sheet was written by Martha C. Monroe and Susan Marynowski, and published by the UF Department of School of Forest Resources and Conservation, September 2012.